YouTube, ensino de bateria e cultura participativa digital : reflexões a partir de dois canais - Potiguara, Lucas Benjamin (2024)
This dissertation investigated the YouTube channels Playing Drums from Scratch and Marques Galles Drumcamp specifically for teaching drums. The research aimed to understand how producers of drum content on YouTube articulate their teaching practices with the specificities of digital participatory culture and as specific objectives: to characterize YouTube as specific to digital participatory culture and a space for teaching and learning music; to know the artistic and training profile of the selected drummers; to analyze the role of video production techniques, formats and content in the teaching practices of drummers; to observe how the participation and interaction between producer and public influence the production of the channels studied. As theoretical references, I bring digital participatory culture and YouTube. YouTube is understood as an environment with its own characteristics of sharing and consuming content, allowing unique teaching and learning experiences, and digital participatory culture represents a dynamic scenario where individuals not only consume, but also produce digital musical content, constantly interacting through creations, comments and discussions, reflecting the diversity of participation and expression in the digital environment. The methodology of this research is qualitative and used the internet as the object, location and instrument of investigation, based on semi-structured interviews conducted online and documentary analysis of some audiovisual productions of the investigated channels. From the data collected, it was possible to perceive that YouTube is much more than a video distribution channel; it is a dynamic and interactive space where educators and musicians adjust their approaches to meet the demands of both the audience and the platform.